Deposition of Polymer Sensor Films on SAW Surface by Electrospraying Technology - JASEK, Krzysztof; PASTERNAK, Mateusz; GRABKA, Michał; NEFFE, Sławomir; ZASADA, Dariusz (Archives of Acoustics, 2017)
One of the most important problems with regard to the Surface Acoustic Wave (SAW) gas sensors technology is the deposition of chemosensitive films exhibiting desirable chemical and physical properties. The electrospraying technology seems to be a very promising method of the film deposition in this case. It allows the chemosensitive layers to be obtained out of almost any chemicals and their mixtures in a controllable way. The process gives the possibility to generate specific films with properties unattainable if other methods were to be applied. For example, it allows to deposit solutions of polymers and suspensions of solids in polymer solutions which can degrade in the process of thermal evaporation deposition. The paper describes the results of experiments with electrospraying technique in order to obtain Nafion® films. The influence of the process parameters on film sensitivity has been studied.